Rewiring Politics : Presidential Nominating Conventions in the Media Age - Panagopoulos, Costas (Book collections on Project MUSE., 2007)
A century ago, national political parties' nominating conventions for U.S. presidential candidates often resembled wide-open brawls, filled with front-stage conflicts and back-room deals. Today, leagues of advisors precisely plan and carefully script these events even though their outcomes are largely preordained. Rewiring Politics offers the first in-depth exploration of the profound changes in the nominating process to focus on the role of the media. Fourteen luminaries from the worlds of media and politics examine how the technology of "coverage" has transformed conventions over time. As the contributors demonstrate, the story of the evolution of the nominating process cannot be told without the concomitant story of the revolution in mass media. The impact of the media on political conventions has received surprisingly little scholarly attention. Yet few aspects of the American political process have faced such radical alterations in such a short period of time. From the first live television broadcast from a national convention on June 21, 1948, during the Republican convention in Philadelphia, through the advent of cable networks and the Internet, both the presentation and the content of the nominating process has been transformed. Today, because the party's nominee is selected before the event, candidates use their conventions-and convention coverage-as a form of advertising. They design mega-media events to electrify the party faithful and to woo undecided voters by dazzling them. Without a doubt, the contributors conclude, conventions still matter, though their role has changed over the past decades. Rewiring Politics helps readers assess the evolution of conventions in contemporary politics and addresses the implications of these changes on our parties, politics, and society